Cropping patterns of shifting cultivation farming in Palasa Highlands, Central Sulawesi, Indonesia. Issue 1 (1st December 2022) - Syafruddin,; Suwitra, I Ketut; Wahyuni, Andi Nirma; Rahayu, Heni SP; Saidah,
Abstract: The research stages consist of identification on potential application of agricultural technology and study on cropping patterns, namely cropping pattern of shallot-shallot-shallot and shallot-peanut- shallot. The research was carried out from November to October 2017 in mountainous area that many farmers were engaged in nomadic farming. The study aims to identify problems and potential land use for the application of agricultural technology and study appropriate cropping patterns to increase income for shifting cultivation. The results showed that the condition of the land was less fertile, very steep slope with traditional existing farming technology, so the risk of crop failure was very high and the land quality decreased very quickly due to the erosion. The results of the analysis of farming feasibility and Marginal Benefit Cost Ratio (MBCR) in the introduction of cropping patterns is very feasible to be developed with B/C and MBCR values more than 1.